Automation in HR and Payroll Systems: An Empirical Study in Poland - Agnieszka JUDKOWIAK; Beata ZALESKA; Krzysztof DZIADEK (Communications of International Proceedings, 2025)
This article aims to analyze research on the extent to which the remuneration calculation function in the surveyed units is performed using IT tools, and to draw conclusions regarding the tendency of these units to automate operations related to remuneration calculation. The study was conducted using the indirect interview method, which involved a questionnaire. Interviews with selected employees of the human resources and payroll departments in public finance units supplemented it.
Keywords: remuneration; HR and payroll processes; automation of payroll calculation; specialized cadastral and payroll programs